VIOLENCE IN AMERICAN CONTEMPORARY DRAMA: A JOHAN GALTUNGIAN READING OF LYNN NOTTAGE’S RUINED - Mohammed, Ahmed (Humanities Journal of University of Zakho, 2025)
The study explores many types of violence placed on the female characters in Lynn Nottage’s Ruined. The researcher attempts to reach the results by conducting a thorough examination of the chosen work. The research investigates how Nottage uses the plot, setting, and characters to convey complex concepts and themes about violence. The study examines the manifestation of violence in Lynn Nottage’s Pulitzer Prize-winning play Ruined (2008) through the lens of Johan Galtung’s theatrical framework of violence. Galtung’s tripartite model encompassing direct, structural, and cultural violence provides a critical tool for analyzing the systemic and multifaceted nature of conflict in the play, which portrays the brutal realities of woman in war-torn Congo. By applying Galtung’s theory, the study highlights how Nottage dramatize not only visible acts of physical and sexual violence (direct violence) but also the entrenched socio-political inequalities (structural violence) and the normalized ideologies that perpetuate oppression (cultural violence). The findings of this study add to the existing body of knowledge of contemporary American Drama and the role of violence in reflecting the social and cultural context of modern American society or even other societies that American Playwrights use to add more universality to the concept of violence. Finally, this study provides a thorough investigation of the use of violence in Contemporary American Theater, using Lynn Nottage’s Ruined as an example. By investigating the role of violence in the aforementioned play, taking into account the social, cultural, and historical conditions in which the play was introduced. The study gives a nuanced understanding of the concept of violence’s significance and its influence on contemporary American Drama.